Laparoscopic removal of migrated IUCD from small intestine in a lactating female patient - Kamboj, Sushmita; Chaudhary, Rachna; Rastogi, Komal; Raj, Dheeraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine perforation is an uncommon complication of intrauterine device insertion, with an incidence of one in 1,000 insertions. Perforation may be complete, with the device totally in the abdominal cavity, or partial, with the device to varying degrees within the uterine wall. Some studies show a positive association between lactation and perforation, but a causal relationship has not been established. Very rarely, a device may perforate into bowel or the urinary tract. Perforated intrauterine devices can generally be removed successfully at laparoscopy.